Disease Pattern and Outcome of Pediatric Patients Admitted in A Non-Government Medical College Hospital - Uddin, Mohammad Shahab; Muhuri, Basana Rani; Hasina Mamtaj, Syeda Shahnoor; Uddin, Mohammed Belal (IAHS Medical Journal, 2022)
Background: An understanding of epidemiological trend in hospital admissions, including diseases and death pattern, is essential for health care planning, appropriate resource allocation and improving existing services facilities. Most of the causes of morbidity and mortality in Pediatric patient particularly under five and neonate are preventable by proper antenatal/perinatal care, early detection and management. To assess the disease pattern and outcome of pediatric patients admitted in a non-government Medical College hospital this research was performed. Materials and methods: This retrospective observational study was conducted at the Department of Child Health, Marine City Medical College Hospital (MCMCH) Chattogram, Bangladesh during 2019 June to 2021 June. A total of 567 patients were included for the study. Details on demographic characteristic, disease pattern, outcome, retrieved from the medical records and admission registers, and tabulated and analyzed using Microsoft Excel (Microsoft Office20 16). Results: Among the admitted patient 0-<2 months age group were (53)9.35%, 2 months-<2 years age group were 254(44.80%), 2 years-<5 years age group were 96(16.93%), 5 years-<12 years age group were 164(28.92%). Among the admitted patients, most common acute watery diarrheawere 131(23.10%), bronchiolitis were 121(21.34%), bronchopneumonia were 95(16.75%), Neonatal Sepsis and Enteric fever were 26(4.59%), Bronchial asthma were 18(3.17%), Low birth weight/preterm were 17(3.00%), Neonaatal Jaundice were 12(2.12%) and others were 92(16.22%). The outcome of total 567 Pediatric patients- discharged with advice were 498(87.83%), discharge on request were 45(7.49%), referred were 20(3.53%) and dead were 4(0.71%). Conclusion: Findings of this study helps us to understand and pediatric admission trend and death pattern of this institution, which are essential for patient’s services, including effective case-management strategies. IAHS Medical Journal Vol 4(2), December 2021; 66-69